(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2023)
During the processing phases of the food business, a large amount of water is used, resulting in a large volume of effluents. Raw materials, sanitary water for food processing, transportation, cooking, dissolving, auxiliary water, cooling, cleaning, and so on are all utilized extensively in the business. Traditional anaerobic or aerobic biological wastewater treatment processes can be employed to handle organic compounds found in food sector effluent. However, some hazardous chemicals to a microbial population may be present in the effluent due to varied consumption. The effluent may contain significant levels of suspended particles, nitrogen in various chemical forms, lipids, oils, phosphorus, chlorides, and high organic content. There are traditional and well-established methods for treating effluents in the food industry, such as the coagulation-flocculation process, electrochemical processes, and biological processes, which have proven to be quite effective when used as treatment methods in a variety of industries; however, such methods have limitations. Innovative techniques, such as microbial fuel cells (MFCs), microalgae, water ultrafiltration, nanofiltration, and membrane technologies, can replace or complement traditional methods in the future. The treatment method chosen will be determined by the industry’s and its wastewater’s characteristics.